Studies on genetic variability among the derived lines of B x B, B x R and R x R crosses for yield attributing traits in rabi sorghum (Sorghum bicolor (L.) MOENCH) - D. G. Shinde, B. D. Biradar, P. M. Salimath, M. Y. Kamatar, A. R. Hundekar and S. K. Deshpande (Electronic Journal of Plant Breeding, 2010)
Studies were carried out to estimate the extent of genetic variability for yield and its component traits among the 120 F6 linesderived from B x B, B x R and R x R crosses in Rabi sorghum at RARS, Bijapur and MARS, Dharwad during rabi 2007-08.Significant mean squares were obtained for yield and its component traits among different groups (B x B, B x R and R x Rderivatives) studied at both locations, thus indicating that the genotypes under study were highly diverse. At both locations,derivatives of B x B and B x R exhibited higher PCV and GCV compared to R x R group for number of grains per panicleand grain yield per plant while R x R derivatives showed high PCV and GCV for these characters; number of primaries perplant, number of grains per panicle and grain yield per plant.Derivatives of B x B and B x R exhibited high heritabilitycoupled with genetic advance for all the characters under study except number of leaves and number of internodes at bothlocations. The R x R derivatives recorded high heritability coupled with genetic advance for the characters viz., plant height,number of leaves, number of internodes, panicle length, panicle breadth, number of primaries, test weight, number of grainsper panicle, fodder yield per plant and grain yield per plant at both the locations. Hence, selection made through thesecharacters would be effective. At both locations, low variability for days to 50 percent flowering was observed among thederivatives of B x B, B x R and R x R crosses, thus suggesting negligible contribution of this trait to total variability.